Intraductal Oncocytic Papillary Neoplasms: Clinical-Pathologic Characterization of 24 Cases, With An Emphasis on Associated Invasive Carcinomas. (May 2019) - Wang, Tao; Askan, Gokce; Adsay, Volkan; Allen, Peter; Jarnagin, William R.; Memis, Bahar; Sigel, Carlie; Seven, Ipek E.; Klimstra, David S.; Basturk, Olca
Abstract : Background: Intraductal oncocytic papillary neoplasm (IOPN) of the pancreas is a rare tumor. Recent molecular data indicate that it is distinct from other intraductal neoplasms; however, its clinicopathologic characteristics, especially the frequency/significance of an invasive carcinoma component, and biologic behavior remain to be fully defined. Design: Clinicopathologic characteristics and survival of 24 IOPNs were analyzed. By definition, all tumors exhibited intraductal growth and oncocytic morphology. Results: The female:male ratio was 1.7, and mean age was 59. In 44% of the patients, the IOPN was discovered incidentally; however, the working diagnosis was "ductal adenocarcinoma" in 42%. Fourteen IOPNs occurred in the head of the pancreas. The median tumor size was 4.5 cm. The tumors often grew along adjacent benign ducts, mimicking invasion, but only 29% exhibited unequivocal invasive carcinoma, mostly in the form of microscopic foci (pT1a=4, pT1b=1, pT2=2), and only 6% had lymph node metastasis. Invasive carcinoma was predominantly composed of small tubular units lined by oncocytic cells, or individual oncocytic cells infiltrating the periductal stroma. Follow-up information was available for 18 patients (median=6.8 y). No patients died from the disease, and the overall 10-year survival was 94%. Patients with invasive carcinoma trended toward a lower 5-year recurrence-free survival than those with noninvasive IOPNs (66% vs. 93%, P =0.066), but overall survival was not impacted by the presence of invasion ( P =0.38). Conclusions: IOPN is a distinct tumor type in the pancreas. Despite its morphologic complexity and often extensive pagetoid spread to adjacent ducts, conventional invasive carcinoma is seen in only 29% and usually as microscopic foci. Thus, it is not surprising that IOPN exhibits indolent behavior even when invasion is present.